PELATIHAN PENULISAN ARTIKEL ILMIAH BAGI MAHASISWA PENDIDIKAN JASMANI UNIVERSITAS MULAWARMAN - Didik Cahyono; Muhammad Rohadi; Nurjamal Nurjamal (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The method of this activity is in the form of training and assistance in writing articles and publishing research results to students of the Physical Education Study Program, Faculty of Teacher Training and Education, Mulawarman University. Final semester students are guided to write articles and publish research results in order to improve their abilities and train students to write and publish the results of the scientific work they make. Based on the results and discussion, it can be concluded that students' interest in writing scientific papers is quite high. However, their initial knowledge of scientific papers and writing methods is still lacking. Therefore, this scientific writing training activity is indeed needed to improve students' knowledge and ability to compile scientific papers.  Participants experienced an increase in knowledge and writing skills.  The results of this service show that this training activity is effective in helping students improve their knowledge and ability to write scientific papers. Training in writing scientific papers can be used as a continuous activity. In addition, currently there are various software for writing references for scientific papers. Therefore, it is necessary to hold training on the use of mandeley software for reference so that writing becomes better